Cytomegalovirus Colitis in Immunocompetent Patients - Inayat, Faisal (Cureus, 2016)
Cytomegalovirus colitis is common in immunocompromised patients, but rare in immunocompetent patients. The present study not only represents the colonoscopy and pathological findings, but also applies the method of diagnosing and treating cytomegalovirus colitis in immunocompetent patients.